PENGARUH SUPERVISI TEKNOLOGI PENDIDIKAN TERHADAP KINERJA TENAGA PENGAJAR - Muhammad Rezki Reza; Syahrani (CV. ADIBA AISHA AMIRA, 2024)
The role of a supervisor is very much expected in training the use of technology to teachers so that it can assist them in completing tasks and making it easier to carry out education in schools. The expertise and skills of a teacher or teacher in operating a technology system at this time is very important, because in this modern era all teachers are required to master technology to make it easier to carry out and complete their work, but in fact there are still many teaching staff who are still lacking. knowledge in operating technology, so to overcome these problems, supervision is needed for teaching staff who are trained by supervisors or people who are experts in accessing and operating a technology.